(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In modern conditions, life insurance plays a crucial role for the economy of the country and its citizens, because it is aimed at financial and social protection of the population through the organization of an integrated system of material security in the event of various events associated with life, health, disability or other events, which can lead to a significant imbalance of family or personal budgets, and a decline in living standards. The main trends of life insurance development in Ukraine presented in the study demonstrate that current processes of globalization have a serious impact on the complications of consumer and savings properties of life insurance through the merger of insurance, credit and investment products. At the same time, in Ukraine, this type of insurance is hampered by a number of factors, due to which it does not become widespread. That is why the article focuses on the problems of life insurance development in the context of financial imbalances and proposes directions for their activation in Ukraine.